Fighting the invisible enemy: public communication on the SARS outbreak in the People's Republic of China and Singapore. - Yeo, Seow Ling. (2008)
This dissertation is about the global outbreak of the Severe Respiratory Syndrome (SARS) in Asia between March and June 2003.